Encryption and Description of RGB Values in Images Using the Hill Chiper Algorithm - Sukma Achriadi; Hardisal; Asmaidi; M. Sulthan Hanafi (LPPM Politeknik Aceh Selatan, 2024)
Information security related to computer use cannot be separated from cryptography. Hill cipher is an application of modulo arithmetic in cryptography. This cryptography technique uses a square matrix as the key used to carry out encryption and decryption. This cryptographic technique was created with the intention of being able to create ciphers (codes) that cannot be broken using frequency analysis techniques. Hill Cipher does not replace each of the same letters in the plaintext with other letters that are the same in the ciphertext because it uses matrix multiplication as a basis for encryption and decryption. Hill Cipher cryptography is a type of classic cryptography that uses a substitution method by providing random keys and the number is the same as the plaintext. The use of encryption and decryption using the Hill cipher algorithm is to help secure data so that it is not easily falsified or accessed by irresponsible people by changing the original image into a different form where the image is not easy to recognize. The encryption and decryption process was designed using the Java programming language using NetBeans 8.2 and the Hill Cipher algorithm to encrypt RGB digital images